2021
DOI: 10.3168/jds.2020-18367
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pregnancy status from mid-infrared spectroscopy in dairy cow milk using deep learning

Abstract: Accurately identifying pregnancy status is imperative for a profitable dairy enterprise. Mid-infrared (MIR) spectroscopy is routinely used to determine fat and protein concentrations in milk samples. Mid-infrared spectra have successfully been used to predict other economically important traits, including fatty acid content, mineral content, body energy status, lactoferrin, feed intake, and methane emissions. Machine learning has been used in a variety of fields to find patterns in vast quantities of data. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
0
30
2
1
Order By: Relevance
“…In the agricultural and animal sciences, uptake of deep-learning techniques has been slow (Howard, 2018). Recently, however, our group applied a deep CNN to MIR spectra-matched pregnancy data and discovered such algorithms significantly improved the prediction accuracy for pregnancy status in dairy cows, a binary phenotype (Brand et al, 2018 Deep-learning tasks are known to require large volumes of data to successfully train a network. Moreover, for supervised learning problems, such as in the present study, there is an additional requirement that data labels must be more or less equally distributed (LeCun et al, 2015;Goodfellow et al, 2016).…”
Section: Harnessing the Power Of Big Data And Artificial Intelligencementioning
confidence: 99%
See 2 more Smart Citations
“…In the agricultural and animal sciences, uptake of deep-learning techniques has been slow (Howard, 2018). Recently, however, our group applied a deep CNN to MIR spectra-matched pregnancy data and discovered such algorithms significantly improved the prediction accuracy for pregnancy status in dairy cows, a binary phenotype (Brand et al, 2018 Deep-learning tasks are known to require large volumes of data to successfully train a network. Moreover, for supervised learning problems, such as in the present study, there is an additional requirement that data labels must be more or less equally distributed (LeCun et al, 2015;Goodfellow et al, 2016).…”
Section: Harnessing the Power Of Big Data And Artificial Intelligencementioning
confidence: 99%
“…We observed that milk MIR spectra contained features relating to pregnancy status and underlying metabolic changes in dairy cows, and that such features can be identified using a deep-learning approach. In our study, we defined pregnancy status as a binary trait (i.e., pregnant, not-pregnant) and found CNN significantly improved prediction accuracy, with trained models able to detect 83 and 73% of onsets and losses of pregnancy, respectively (Brand et al, 2018). More recently we have improved prediction accuracy such that models predict pregnancy status with an accuracy of 97% (with a corresponding validation loss of 0.08) after training for 200 epochs (our unpublished data).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pregnancy results in changes to metabolism and energy requirements and leads to a repartitioning of resources to different physiological functions, compared with a nonpregnant lactating animal, and has a consequent influence on milk composition in dairy cattle, particularly in mid to late lactation (Olori et al, 1997;Loker et al, 2009;Penasa et al, 2016). Previous studies have examined the effect of pregnancy stage on detailed milk composition as determined by FT-MIR spectra (Lainé et al, 2017), and have reported the ability to predict conception outcomes (Hempstalk et al, 2015) or pregnancy (Toledo-Alvarado et al, 2018;Delhez et al, 2020;Brand et al, 2021) from FT-MIR spectra. Improvements in accuracy from incorporating FT-MIR data into pregnancy prediction models vary between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning methods have been widely used in similar settings [13]. Examples include: detection of pregnancy status [14], bovine tuberculosis status [15], milk quality traits in dairy farms [16] and the risk of developing metritis, hyperketonemia and mastitis after calving by using the prepartum behaviour [17]. These methods can discover complex, latent patterns between predictor variables and the trait of interest-the disease status, in our work-even if this relationship is non-linear.…”
Section: Introductionmentioning
confidence: 99%